Guanidinium‐Assisted Surface Matrix Engineering for Highly Efficient Perovskite Quantum Dot Photovoltaics. Issue 26 (25th May 2020) - Ling, Xufeng; Yuan, Jianyu; Zhang, Xuliang; Qian, Yuli; Zakeeruddin, Shaik M.; Larson, Bryon W.; Zhao, Qian; Shi, Junwei; Yang, Jiacheng; Ji, Kang; Zhang, Yannan; Wang, Yongjie; et al.
Abstract: Metal halide perovskite quantum dots (Pe‐QDs) are of great interest in new‐generation photovoltaics (PVs). However, it remains challenging in the construction of conductive and intact Pe‐QD films to maximize their functionality. Herein, a ligand‐assisted surface matrix strategy to engineer the surface and packing states of Pe‐QD solids is demonstrated by a mild thermal annealing treatment after ligand exchange processing (referred to as "LE‐TA") triggered by guanidinium thiocyanate. The "LE‐TA" method induces the formation of surface matrix on CsPbI3 QDs, which is dominated by the cationic guanidinium (GA + ) rather than the SCN −, maintaining the intact cubic structure and facilitating interparticle electrical interaction of QD solids. Consequently, the GA‐matrix‐confined CsPbI3 QDs exhibit remarkably enhanced charge mobility and carrier diffusion length compared to control ones, leading to a champion power conversion efficiency of 15.21% when assembled in PVs, which is one of the highest among all Pe‐QD solar cells. Additionally, the "LE‐TA" method shows similar effects when applied to other Pe‐QD PV systems like CsPbBr3 and FAPbI3 (FA = formamidinium), indicating its versatility in regulating the surfaces of various Pe‐QDs. This work may afford new guidelines to construct electrically conductive and structurally intact Pe‐QD solids for efficient optoelectronic devices. Abstract : A ligand‐assisted matrix to regulate surface and packing states of perovskite quantum dots (QDs) is demonstrated, which involves a ligand exchange and a mild thermal annealing process that are triggered by guanidinium thiocyanate. Consequently, the CsPbI3 QD solar cells (QDSCs) deliver a champion power conversion efficiency of 15.21%, which is the highest report among all CsPbI3 QDSCs.